Evaluation of Polyethylene Glycol Crosslinked β-CD Polymers for the Removal of Methylene Blue - Isabelle Mallard; David Landy; Sophie Fourmentin (Applied Sciences, 2020)
The environment is at the heart of global worldwide discussion. This study describes the synthesis of ecofriendly polymers by a crosslinking reaction between β-cyclodextrin as the monomer and polyethylene glycol diglycidyl ether (PEDGE) as well as ethylene diglycidyl ether (EDGE) as the crosslinking agents. The studied polymers were characterized by several techniques, such as SEM, FTIR, TGA-TDA and XRD. Their adsorption properties for methylene blue under various conditions of pH, contact time and initial concentration of dye were assessed in order to find the optimal conditions. The results indicate that the polymers are good nominates for methylene blue adsorption with adsorption capacities up to 15 mg/g. The adsorption mechanism was demonstrated to follow the Langmuir model. Finally, the regeneration of the polymers was investigated using Soxhlet extraction with ethanol. The absorption capacities of the adsorbent were stable after three cycles.